The VP6 Protein of Rotavirus Interacts with a Large Fraction of Human Naive B Cells via Surface Immunoglobulins - Parez, Nathalie (American Society for Microbiology, 2004)
Immunity to human group A rotavirus (RV), a major cause of viral gastroenteritis in infants, involves B lymphocytes that provide RV-specific antibodies. Additionally, some arguments suggest that naive B cells could be implicated in the first steps of the immune response against RV. The aim of our study was to analyze the interaction of VP6 and VP7 RV capsid proteins with human B cells depending on the immune status of the individual, i.e., naive or RV experienced. For this purpose, a two-color virus-like particle flow cytometry assay was devised to evaluate the blood B-lymphocyte reactivity to VP6 and VP7 proteins from healthy RV-exposed adults, recently infected infants, and neonates at birth. Both VP6 and VP7 interactions with B cells were mediated by surface immunoglobulins and probably by their Fab portions. VP7-reactive B lymphocytes were mainly detected from RV-experienced patients and almost exclusively in the CD27-positive memory cell fraction. Conversely, VP6-reactive B lymphocytes were detected at similar and high frequencies in adult, infant, and neonate samples. In adult samples, VP6 reacted with about 2% of the CD27-negative (CD27(neg)) naive B cells. These results demonstrated that the VP6 RV protein interacted with a large fraction of naive B lymphocytes from both adults and neonates. We propose that naive B cell-VP6 interaction might influence the strength and quality of the acquired immune response and should be considered for elaborating RV vaccine strategies.